Pengaruh Dukungan Organisasi dan Kepuasan Kerja Terhadap Retensi Karyawan Pada Home Industry Percetakan Jasa Cetak Satria Semarang - Rossiana Octa Attika; Sri Suprapti; Gita Sugiyarti; Syahtri Wardana Priyambodo (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to examine the effect of organizational support and job satisfaction on employee retention at Home Industry Percetakan Jasa Cetak Satria. Employee retention is a crucial factor for business sustainability, as it is closely related to workforce stability and operational effectiveness, particularly in small-scale enterprises. The population of this study consists of all 35 active employees of Home Industry Percetakan Jasa Cetak Satria. A quantitative approach was employed, with a census method used for sampling. Data were collected through questionnaires using a five-point Likert scale and analyzed using multiple linear regression. The results show that organizational support has a positive and significant effect on employee retention with a significance value of 0.011, while job satisfaction also has a positive and significant effect with a significance value of 0.040. This study confirms that improving organizational support and job satisfaction can enhance employee retention.